Pengaruh Model Pembelajaran Contextual Teaching and Learning terhadap Hasil Belajar Siswa pada Mata Pelajaran IPAS Kelas III SDN 2 Gerimak Indah - Astri Susanti; Muhammad Sobri; Ilham Handika (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The low learning outcomes in Science and Social Studies (IPAS) among third-grade students were evident during the learning process. Many students were less active and paid less attention to the teacher's explanations. This study aims to determine the effect of implementing the Contextual Teaching and Learning (CTL) model on student learning outcomes in the IPAS subject at SDN 2 Gerimak Indah. This research employs a quantitative approach with an experimental design. The population includes all third-grade students at SDN 2 Gerimak Indah. Data were collected through observations and tests to measure cognitive learning outcome indicators, which include remembering (C1), understanding (C2), applying (C3), and analyzing (C4). Observation results showed that the implementation of the CTL model syntax was executed very well in the classroom. The findings indicated a significant increase in IPAS learning outcomes, with the average post-test score reaching 85.45, compared to the initial pre-test average of only 54.54. Improvement occurred across all measured cognitive indicators. Based on these results, it can be concluded that the application of the CTL model has a significant positive effect on students' IPAS learning outcomes and is capable of increasing student engagement in the learning process.